서부 경기육괴에 분포하는 태안층의 퇴적시기와 기원지에 대한 고찰 - 최태진(Taejin Choi); 박승익(Seung-Ik Park) (자원환경지질, 2019)
Various studies regarding the sedimentary environment, depositional age, provenance, and metamorphic history have been carried out on the Taean Formation in the western part of Gyeonggi Massif, since the unique detrital zircon age pattern was revealed. This review paper introduces the previous researches on the Taean Formation and discusses the depositional age and provenance. The Taean Formation was traditionally regarded as a Precambrian stratigraphic unit, but recently it is interpreted to be a middle or upper Paleozoic formation due to the occurrence of large amounts of Early to Middle Paleozoic detrital zircons. The Taean Formation consists of metasandstone, argillaceous schist, and phyllite which are mainly made up of quartz and mica. The protoliths are interpreted as turbidites deposited in deep sea fan environment. The Taean Formation has been interpreted to be deposited between the Devonian to Triassic ages given the age differences between detrital zircons and intrusive rocks. There are two opinions that the deposition age is close to the Devonian or the Permian period. The provenance of this formation is supposed to be South China block, Chinese collisional belt, or Gyeonggi Massif. Given the available detrital zircon ages of the Taean Formation and other Korean (meta)sedimentary rocks, the Taean Formation shares major source rocks with Yeoncheon Group and Pibanryeong Unit of the Okcheon Supergroup, but their source regions are not entirely consistent. Considering the existing hypotheses about the depositional timing and provenance, we put weight on the possibility that the Taean Formation was deposited between Permian and Early Triassic periods. However, further studies on the stratigraphy and sedimentary petrology are needed to clarify its definition and to elucidate the provenance. 경기육괴 서부에 분포하는 태안층의 독특한 쇄설성 저어콘 연대 분포가 알려진 이후 퇴적환경, 퇴적시기, 기원지, 변성사 등에 대한 다양한 연구가 이루어졌다. 이 논평에서는 그 동안 태안층에 대하여 이루어진 기존 연구들을 소개하고 퇴적시기 및 기원지에 대하여 고찰하고자 한다. 태안층은 전통적으로 선캠브리아시대의 지층으로 알려졌으나, 근래 다수의 전기-중기 고생대 저어콘들이 발견된 이후 중부 혹은 상부 고생대 퇴적층으로 해석되고 있다. 태안층은 주로 석영과 운모로 구성된 변성사암, 이질편암, 천매암으로 구성되었으며, 이들의 원암은 심해선상지의 로브 환경에서 쌓인 저탁암으로 해석되었다. 태안층이 퇴적된 시기는 쇄설성 저어콘 연령과 관입암의 연령 차이를 통해 데본기-트라이아스기 사이로 알려져 있는데, 퇴적시기가 데본기에 가깝다는 견해와 페름기에 가깝다는 견해로 나뉜다. 태안층의 기원지는 남중국지괴나 중국의 충돌대, 또는 경기육괴로 추정되고 있다. 태안층과 기타 한반도 (변성)퇴적층의 쇄설성 저어콘 연대를 다룬 기존 연구들의 자료를 비교한 결과, 태안층은 연천층군이나 옥천누층군의 피반령 단위와 주요 기원암을 공유하되 기원지가 완전히 일치하지는 않는 것으로 여겨진다. 이러한 결과를 바탕으로 태안층의 퇴적시기와 기원지에 대한 기존 가설들을 고려하면, 태안층을 페름기-전기 트라이아스기 사이에 퇴적된 것으로 해석한 모델이 비교적 합리적으로 보인다. 향후 태안층의 정의를 명확히 하고 기원지 규명을 위한 층서학 및 퇴적암석학적 추가연구가 필요하다.